2012
DOI: 10.1016/j.crvi.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, insulin resistance and diabetes in the sand rat exposed to a hypercaloric diet; possible protective effect for IL1-β

Abstract: Animal biology and pathology/Biologie et pathologie animales Obesity, insulin resistance and diabetes in the sand rat exposed to a hypercaloric diet; possible protective effect for IL1-bObe´site´, insulinore´sistance et diabe`te chez le rat des sables soumis a `un re´gime hypercalorique ; ro ˆle protecteur possible de IL-1b

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…SO was considered as a control group (C-SO), mainly because it contains adequate levels of PUFA, n − 6/n − 3 ratio within acceptable limits [38][39][40], and by its elevated consumption worldwide [25,37]. The two experimental groups (C-SO and HVF) were isocaloric in order to prevent metabolic differences between animals of different experimental groups [41,42] from interfering with the antioxidant defense system [43] and dopamine and serotonin neurotransmission [44]. The consumption of the diets was monitored every other day.…”
Section: Methodsmentioning
confidence: 99%
“…SO was considered as a control group (C-SO), mainly because it contains adequate levels of PUFA, n − 6/n − 3 ratio within acceptable limits [38][39][40], and by its elevated consumption worldwide [25,37]. The two experimental groups (C-SO and HVF) were isocaloric in order to prevent metabolic differences between animals of different experimental groups [41,42] from interfering with the antioxidant defense system [43] and dopamine and serotonin neurotransmission [44]. The consumption of the diets was monitored every other day.…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of spontaneously obesity in the Meriones unguiculatus species of gerbils was reported several decades ago, when researchers observed that 10% of the animals became obese and showed metabolic alterations, even when fed standard diet (Vincent, Rodrick & Sodeman jr, 1979). Other species of desert rats, or gerbils, may also develop obesity when their typical diet is changed to standard rodent chow, such as Psammomys obesus (Khalkhal et al, 2012). Some studies addressed metabolic and immunological disorders related to obesity in this model of naturally obese animals (Xu, Liu & Wang, 2011; Liu, Xu & Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…IL-1 modulates glucose homeostasis by impairing insulin signaling, modulating insulin secretion, augmenting insulinindependent glucose uptake, increasing energy expenditure, and stimulating autonomic nervous system activity (58,70,97,107). Depending on the dose, IL-1 can induce hypoglycemia or hyperglycemia (70,138).…”
Section: Inflammation: Impact On Energy Expenditure and Glucose Homeomentioning
confidence: 99%